OPTIMUM ENERGY CALCULATION FOR A DRILL HAMMER BLOW RH571 4W - Souilah, N; Zahzouh, Z (university of el oued/جامعة الوادي, 2021)
Consumption of raw materials has steadily increased. Rich countries explore several raw materials such as phosphate, ore and copper. For this, exploitations must be large, hig hly mechanized and produce in lar ge quantities to be profitable. Also, the use of drilling means requires good productivity on the one hand and a long service life on the other hand. The satisfaction of these requirements is possible if the drilling method ch osen is suitable for the geological and mining conditions as well as the drilling parameters . The choice of the machine therefore has a direct impact on costs and results. The aim of this work is to ensure a proper exploitation with an optimum energy ca lcu lation for a drill hammer blow taking into account their economic or technical conception characteristics. To find out the energy losses of a hammer blow, the Baron and Ghrainer formula which , has been applied allows us to calculate the drilling speed and to deduce the blow energy. Then, to calculate the energy losses and to extract the optimal values for different parameters, a statistical model of GAUSS MARKOV theorem has been introduced
Article
Keywords: Keywords: Hammer drill ; statistical model ; Drilling speed; Roc k; E nergy of a blow